The lazy detective - Dilnot, George, 1883-1951 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Lazy Detective" by George Dilnot is a detective novel written in the early 20th century. The story follows Divisional Detective Inspector Harry Labar, whose idleness earns him the reputation of being lazy among his peers at Scotland Yard. He gets embroiled in a complex case involving a high-profile jewel heist linked to the enigmatic crime organizer Larry Hughes, while also navigating the complications of his own lethargy and the pressures from his superiors. At the start of the novel, Inspector Labar faces discontent from his Chief Constable regarding the rising crime rates in his division. Labar's tenuous position is further complicated when he receives an unexpected bribe in the form of a hundred-pound note handed to him by a mysterious woman in a car. As he begins to investigate the recent burglary at the residence of millionaire Solly Gertstein, it becomes evident that he is dealing with skilled criminals. The narrative introduces suspenseful elements, including potential connections to Hughes and his dubious associates, and hints at a deeper personal entanglement involving Labar and Miss Penelope Noelson, Gertstein$1 (Bs companion, as they all navigate the disconcerting world of crime and deception. (This is an automatically generated summary.)s
Release date is 2025-03-01
Tim Miller, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Detective and mystery stories; Jewelry theft -- Fiction; Criminals -- Fiction; Police -- England -- London -- Fiction